Subwavelength engineering and asymmetry: two efficient tools for sub-nanometer-bandwidth silicon Bragg filters - Oser, Dorian; Pérez-Galacho, Diego; Alonso-Ramos, Carlos; Le Roux, Xavier; Tanzilli, Sébastien; Vivien, Laurent; Labonté, Laurent; Cassan, Éric (Optical Publishing Group, 2018)
Bragg filters stand as a key building blocks of the silicon- on-insulator (SOI) photonics platform, allowing the implementation of advanced on-chip signal manipulation. However, achieving narrowband Bragg filters with large rejection levels is often hindered by fabrication constraints and imperfections. Here, we show that the combination of single-side corrugation asymmetry and subwavelength engineering provides narrowband response with large corrugations, overcoming minimum feature size constraints of conventional Si Bragg filters. We comprehensively study the impact of the corrugation asymmetry in conventional and subwavelength single- etched SOI Bragg filters, showing their potential for bandwidth reduction. Finally, we experimentally demonstrate a novel subwavelength geometry, based on shifted corrugation teeth, achieving null-to-null bandwidths and rejections of 0.8 nm and 40 dB for the symmetric configuration, and 0.6 nm and 15 dB for the asymmetric case.
Keywords: Comunicaciones ópticas; Bragg reflectors; Subwavelength structures; Integrated optics materials